2021
DOI: 10.1002/mmce.22709
|View full text |Cite
|
Sign up to set email alerts
|

A 2 × 1 array‐based wideband mm‐wave antenna integrated with a 2‐element multiple‐input‐multiple‐output antenna for 5G mobile terminals

Abstract: A novel wideband millimeter (mm)-wave antenna integrated with a multi-input multi-output (MIMO) antenna is presented for fifth-generation (5G) applications.The proposed model consists of a 2 Â 1 array-based single-element wideband antenna for mm-wave applications, and a 2-element strip-based MIMO antenna system for sub-6-GHz band applications. In the ground plane, two clearance regions were etched to improve the impedance matching of MIMO elements while an open-circuit rectangular tuning stub is attached to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…As MIMO allows multiple antennas to radiate simultaneously, enhancing the channel capacity and data rates with multi-Gbps throughput (required for 5G systems), therefore, it draws the attention of researchers, and in recent years MIMO has been widely studied. Numerous works have been reported with MIMO antenna designs operating at 5G sub-6 GHz [60][61][62][63][64][65][66]. Sarkar et al [60] suggested a four-element MIMO structure consisting of inverted L-shaped monopole antennas, as shown in Figure 14.…”
Section: Figure 10mentioning
confidence: 99%
See 1 more Smart Citation
“…As MIMO allows multiple antennas to radiate simultaneously, enhancing the channel capacity and data rates with multi-Gbps throughput (required for 5G systems), therefore, it draws the attention of researchers, and in recent years MIMO has been widely studied. Numerous works have been reported with MIMO antenna designs operating at 5G sub-6 GHz [60][61][62][63][64][65][66]. Sarkar et al [60] suggested a four-element MIMO structure consisting of inverted L-shaped monopole antennas, as shown in Figure 14.…”
Section: Figure 10mentioning
confidence: 99%
“…In addition, the impact of the user's hand on the antenna performance and SAR analysis is also carried out. Another MIMO antenna system composed of four dielectric-loaded horn antennas is reported in [65] for vehicle-to-everything communication at 5G sub-6 GHz frequencies. Likewise, the study in [66] reported a four-element MIMO antenna system for 5G devices with the orthogonal placement of antennas.…”
Section: Figure 10mentioning
confidence: 99%
“…The channel capacity loss is an indicator for understanding the change in capacity due to the MIMO environment. The CCL for the MIMO antenna can be calculated by the equation reported in Equation (7), provided in [26,27].…”
Section: Channel Capacity Loss (Ccl)mentioning
confidence: 99%
“…This forces the researcher towards the exploration of the mmWave spectrum, which has the advantages of wider bandwidth capable of providing higher data rates in comparison to sub 6 GHz bands [3,4]. The electromagnetic (EM) waves radiating at the mmWave spectrum may face various issues, including multipath fading and atmospheric absorption losses [5][6][7]. To deal with these wireless network limitations, the researcher in [8][9][10], suggested MIMO and antenna arrays to be one of the solutions which can overcome the limitations faced by mmWave band spectrums.…”
Section: Introductionmentioning
confidence: 99%
“…The International Telecommunication Union and Federal Communication Commission (FCC) propose the mm-wave band with a minimum of 500 MHz bandwidth for 5G applications, prompting researchers to explore the mm-wave spectrum for its wider bandwidth and potential for higher data rates than sub-6 GHz bands [5]- [7]. However, electromagnetic waves in the mm-wave spectrum encounter challenges like multipath fading and atmospheric absorption losses [8]. Researchers propose multiple-inputmultiple-output (MIMO) and antenna arrays as solutions to overcome these limitations.…”
Section: Introductionmentioning
confidence: 99%